2015
DOI: 10.4013/nbc.2015.103.09
|View full text |Cite
|
Sign up to set email alerts
|

Are breeding sites a limiting factor for the Tandilean redbelly toad (Bufonidae) in pampean highland grasslands?

Abstract: The selection of breeding sites in response to temporary pond characteristics has been frequently documented in several anuran species. Small and shallow temporary ponds are usually preferred. The Tandilean red-belly toad, Melanophryniscus aff. montevidensis, is an endemic species that breeds in temporary ponds of remnants of highland grasslands in Tandilia mountain system, Buenos Aires Province, Argentina. The goals of this work are to characterize breeding sites of Tandilean red-belly toad, and to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…montevidensis belongs to the M. stelzneri group. It inhabits a narrow corridor of sandy dunes along the Rio de la Plata shoreline and Atlantic coast in Uruguay (Langone 1995, Núñez et al 2004, Maneyro and Kwet 2008 and Alvorada (Barra do Chui) at the southern extreme of Rio Grande do Sul, Brazil (Tedros et al 2001, Bernardo-Silva et al 2012 (Cairo et al 2008, Cortelezzi et al 2015, Friedman et al 2016, Kacoliris et al 2017. In older works these populations were assigned to the Uruguayan species M. montevidensis based on coloration similarities (Cei 1980, Gallardo 1987, Gallardo and Varela de Olmedo 1992, but Klappenbach and Langone (1992), based on geographical distribution, concluded that they could be different species, a hypothesis supported by Cespedez et al (2000).…”
Section: Introductionmentioning
confidence: 99%
“…montevidensis belongs to the M. stelzneri group. It inhabits a narrow corridor of sandy dunes along the Rio de la Plata shoreline and Atlantic coast in Uruguay (Langone 1995, Núñez et al 2004, Maneyro and Kwet 2008 and Alvorada (Barra do Chui) at the southern extreme of Rio Grande do Sul, Brazil (Tedros et al 2001, Bernardo-Silva et al 2012 (Cairo et al 2008, Cortelezzi et al 2015, Friedman et al 2016, Kacoliris et al 2017. In older works these populations were assigned to the Uruguayan species M. montevidensis based on coloration similarities (Cei 1980, Gallardo 1987, Gallardo and Varela de Olmedo 1992, but Klappenbach and Langone (1992), based on geographical distribution, concluded that they could be different species, a hypothesis supported by Cespedez et al (2000).…”
Section: Introductionmentioning
confidence: 99%